Mec1/ATR regulates the generation of single-stranded DNA that attenuates Tel1/ATM signaling at DNA ends - Clerici, Michela (Blackwell Publishing Ltd, 2014)
Tel1/ATM and Mec1/ATR checkpoint kinases are activated by DNA double-strand breaks (DSBs). Mec1/ATR recruitment to DSBs requires the formation of RPA-coated single-stranded DNA (ssDNA), which arises from 5′–3′ nucleolytic degradation (resection) of DNA ends. Here, we show that Saccharomyces cerevisiae Mec1 regulates resection of the DSB ends. The lack of Mec1 accelerates resection and reduces the loading to DSBs of the checkpoint protein Rad9, which is known to inhibit ssDNA generation. Extensive resection is instead inhibited by the Mec1-ad mutant variant that increases the recruitment near the DSB of Rad9, which in turn blocks DSB resection by both Rad53-dependent and Rad53-independent mechanisms. The mec1-ad resection defect leads to prolonged persistence at DSBs of the MRX complex that causes unscheduled Tel1 activation, which in turn impairs checkpoint switch off. Thus, Mec1 regulates the generation of ssDNA at DSBs, and this control is important to coordinate Mec1 and Tel1 signaling activities at these breaks.